Assessing internal processes of a community-based microfinance model to alleviate extreme poverty in society - Khalequzzaman, Mohammad; Ab Rahman, Asmak; Kamsin, Amirrudin (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
The Sharīʿah-based and Information and Communication Technology (ICT)-driven Microfinance Model (SIMM) represents a community-oriented initiative designed to combat severe poverty within society. A notable limitation of existing microfinance institutions (MFIs) is their inability to incorporate extremely impoverished individuals into their client base. This longitudinal study employed a quantitative methodology to assess the internal processes of SIMM through a pilot study involving 421 rural households in Kalainagar village, Bangladesh. The evaluation of SIMM’s internal processes was grounded in five critical factors: microfinance model (MFM), ICT utilization, investment values (IV), entrepreneurial values (EV), and business values (BV). To explore the interrelationships among these factors, Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. The findings revealed significant and positive relationships among the constructs. Additionally, a robustness test was conducted to further substantiate the internal processes of SIMM. As a community-based microfinance model, SIMM exhibits substantial potential for alleviating extreme poverty in rural communities.